Sulphur Dioxide Emission Dispersion Modelling from a Coal Fired Power Plant in Canakkale, Turkey - Yavuz, Elif; Kuzu, S. Levent; Saral, Arslan (Mehmet Sinan Bilgili, 2020)
Sulphur dioxide is originated from the combustion of sulphur-containing fuel. Coal is a major source of sulphur content. Therefore, special emphasis is present for coal combustion. In this study, we aimed to calculate stack emission distribution at ground-level receptor points. For this purpose, we executed AERMOD. As being a preliminary study, our model domain was 25 km x 25 km with 250 m grid spacing. An air quality monitoring station is available within our study domain. It was processed as a discrete receptor point, which gave us the opportunity to compare the estimated results. The year of 2014 was selected as the calculation period in order to compare with the previous studies. The annual average of sulphur dioxide emissions at the receptor was 0.4 mu g/m(3). The average of monitored sulphur dioxide 13.2 mu g/m(3). The share of the power plant borne emissions remained quite low. The principal reason may be the wind distribution at the meteorological station. The dominant wind direction was southeast and the second dominance was for northeast direction. The distance between meteorological station and the pollutant source can affect the calculation results. As a conclusion, the authors propose the use of mesoscale weather forecasting systems to accurately calculate the dispersion of pollutants. Additionally, the authors suggest the use of computational fluid dynamic methods for calculation of single point dispersion at the downwind of the pollutant source.
Keywords: AERMOD; Power plant; Sulphur dioxide; RISK; Engineering; Environmental Sciences & Ecology